Electrochemical study of the inhibition effect of cow bone ash on the corrosion resistance of mild steel in artificial concrete pore solution. Issue 1 (1st January 2019) - Loto, Roland Tolulope; Busari, Ayobami
Abstract: Substitution of cement powder with sustainable waste products is the focus of research in concrete technology. Cow bone ash (CBA) was studied to determine its inhibition effect on Mild Steel corrosion in artificial concrete pore solution by potentiodynamic polarization technique (between potentials of −1 V and + 1.75 V and scan rate of 0.0015 V/s) and current–time displacement method. Results showed CBA significantly decreased the corrosion rate of the steel with peak inhibition efficiency of 80.18% at 20% CBA concentration and polarization resistance of 20, 570 Ω. CBA exhibits anodic type inhibition. The cathodic branch of the polarization curve shows significant decrease in slope after 0% CBA. CBA decreases the pitting corrosion resistance of mild steel at lower concentrations while higher concentrations of CBA decrease the pitting current of the steel adding no additional advantage. Current time displacement shows CBA decreases the thermodynamic instability of the passive film on the steel with respect to concentration and the tendency of the steel to corrode.